2023
DOI: 10.2196/43771
|View full text |Cite
|
Sign up to set email alerts
|

Implementation of a Web-Based Resilience Enhancement Training for Nurses: Pilot Randomized Controlled Trial

Abstract: Background Global workforce challenges faced by health care providers are linked to low levels of job satisfaction, recruitment, retention, and well-being, with detrimental impacts on patient care outcomes. Resilience-building programs can provide support for staff who endure highly stressful environments, enhance resilience, and support recruitment and retention, with web-based formats being key to increasing accessibility. Objective We aimed to examin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 8 publications
(2 citation statements)
references
References 42 publications
(84 reference statements)
0
1
0
Order By: Relevance
“…This study highlights the need for health care organizations to go beyond providing institutional support to recognize the importance of individual resources and provide tools and support to promote individual resilience. Such support can take the form of employee assistance programs, mental health support, peer support resources [ 11 , 29 ], wellness programs [ 30 ], and training to help staff manage their personal resources and cope with the stress of their work [ 31 ]. In situations such as the pandemic, where social distancing is crucial, digital tools can be a useful way to provide emotional and psychological support [ 32 ].…”
Section: Discussionmentioning
confidence: 99%
“…This study highlights the need for health care organizations to go beyond providing institutional support to recognize the importance of individual resources and provide tools and support to promote individual resilience. Such support can take the form of employee assistance programs, mental health support, peer support resources [ 11 , 29 ], wellness programs [ 30 ], and training to help staff manage their personal resources and cope with the stress of their work [ 31 ]. In situations such as the pandemic, where social distancing is crucial, digital tools can be a useful way to provide emotional and psychological support [ 32 ].…”
Section: Discussionmentioning
confidence: 99%
“…Nurses showed enthusiasm for implementing such programs to optimize their resilience levels as well as improve their mental health status communication skills and work environment. [24] In addition, a team of Chinese researchers led by Shao Haiyan, Han Peng, Jiang Jinxia, Duan Xia, and Liu Yue had dedicated their research to exploring the factors that influence the psychological resilience of critical care or emergency nurses during the COVID-19 pandemic. Their studies had demonstrated that adequate pre-outbreak preparation, well-planned arrangements, a supportive working environment built on trustworthiness, encouragement and enhancement of individual and collective coping strategies for nurses in facing adversity, timely recognition and rewards, and empowerment of nurses through counseling and training can effectively enhance their psychological resilience.…”
Section: Analysis Of Important Research Forces and Research Directionsmentioning
confidence: 99%